Biomechanics of Training and Testing Innovative Concepts and Simple Field Methods (Springer International Publishing, 2018)
This book presents an account of innovative methods and, for most of them, gives direct and practical insights into how practitioners can benefit from their use in their everyday practice. It also explains how to interpret the data measured, and the underlying neuromechanical and biomechanical factors related to sports performance. Written and edited by the same researchers who proposed and validated these methods, this book not only presents innovative methods for an efficient training and testing process (most of which are based on very simple technology and data processing methods), but also discusses the associated background information. Although it is a young scientific discipline, sport biomechanics has taken on an important role in routine sports training, medicine and rehabilitation. It allows both a better understanding of human locomotion and performance and better design of training and injury prevention. In those processes, the testing of athletes is crucial, and the quality and quantity of the variables analysed directly influences the efficiency of physicians', coaches', physiotherapists' and other practitioners' interventions.